BREAKING THE CHAIN OVERCOMING, UNDERSTANDING, PREVENTING AND ERADICATING SEXUAL HARASSMENT IN INDONESIA - Fadhillah Mahendra; Violin Revalika Arwis (President University, 2020)
This abstract focus on sexual harassment case in Indonesia, “Breaking the Chain Overcoming, Understanding, Preventing and Eradicating Sexual Harassment in Indonesia”. Sexual harassment cases are common cases that occur not only in Indonesia, but also in the world. Cases of sexual harassment also often receive the attention of the public, state officials and the law. Even though there is a legal framework in Indonesia, low incident reporting is still a challenge. This highlights the need for a comprehensive understanding of the cultural nuances that shape perceptions and responses to such behavior. Cases of sexual harassment do not only happen to women, but also to men. Those who became victims also came from various ages, from toddlers to even the elderly. This abstract will be focus on aims why we need to minimize cases of sexual harassment in Indonesia.ArticleAbstract Keywords: Sexual Harassment, Indonesia, Legal Framework, Social-Culture Society.